Selection of guided surgery dental implant systems using network data envelopment analysis - I-Fei Chen; Chien-Chih Wang; Shui-Lien Chen; Yu-Chin Kao (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
All dental implant system suppliers typically claim the advantages and superiority of their product's specific attributes and functions. However, as assessment criteria are often inconsistent and conflicting, clinical dentists find it difficult to choose the most appropriate dental implant system. The present study used two-stage data envelopment analysis to measure the overall efficiency of individual dental implant systems and the relative efficiency of each phase of the selection process. The results of the present study can not only provide decision-making information for users, such as medical organizations, dentists, and patients, but may also inform guidelines for system producers to improve dental implant performance.
Keywords: 330; Frontier projection; two-stage DEA; supplier selection; dental implant system